LU laika dienests attēlos: virtuālā izstāde - Vilka, Gunta (LU Muzejs, 2024)
Latvijas Universitātes Astronomiskās observatorijas laika dienests attēlos ar komentāriem – virtuālā izstāde.
The precise time service of the Astronomical Observatory of the University of Latvia in images with comments - a virtual exhibition.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics::Astronomy and astrophysics::Astronomy; Latvijas Universitāte; Latvijas Universitātes Astronomiskā observatorija; Astronomija; Laika dienests; Precīzie pulksteņi; The University of Latvia; Astronomical Observatory of the University of Latvia; Astronomy; Time Service; Precision clocks